Survival and Disease Progression in Older Adult Patients With Cirrhosis: A Retrospective Study - Khaled Al-Smadi; Ammar Qureshi; Michelle Buitrago; Besher Ashouri; Zeid Kayali (International Journal of Hepatology)
Conclusions: Cirrhotic patients aged ≥ 65 years have significantly poor survival compared to younger patients. A prospective study is needed to further investigate the effect of age and obesity on survival and disease progression in older adult patients with cirrhosis.